Cultivating Ecological Stewardship: Integrating the Adiwiyata Program with Islamic Religious Education in an Indonesian Vocational School - Alwi, Itsnaini Muslimati; Haris, Abdul (PPSDP International Journal of Education, 2026)
Environmental Education programs like Indonesia’s Adiwiyata are widely implemented, yet their integration with faith-based curricula to foster ecological stewardship has received little scholarly attention. This study aims to describe the implementation of adiwiyata material in PAI learning and its implications for students at State Vocational High School 2 Pacitan. A qualitative case study was conducted at a nationally recognized Adiwiyata school, utilizing semi-structured interviews with teachers, classroom observations, and document analysis. The results showed: (1) Environmental conservation is carried out by Vacational High School 2 Pacitan through the existence of green open spaces, green houses, family medicinal plants (toga), ablution water waste management, and waste management through waste banks, and others, (2) The implementation of adiwiyata materials in PAI subjects is carried out by integrating through learning, which includes planning, implementation, and evaluation. (3) Some of the implications resulting from the cultivation of environmental awareness in State Vocational High School 2 Pacitan students include: (a) realizing interaction for students with the environment, (b) developing students’ ecological awareness, (c) strengthening students’ environmental ethics.